2018
DOI: 10.1111/jvim.15239
|View full text |Cite|
|
Sign up to set email alerts
|

Spontaneous primary hypothyroidism in 7 adult cats

Abstract: BackgroundNaturally occurring hypothyroidism in adult cats is rare, with only 4 cases reported.ObjectivesTo describe the historical, clinical, laboratory, and scintigraphic features of adult cats with spontaneous hypothyroidism.AnimalsSeven adult cats referred for suspected hypothyroidism.MethodsProspective case series. We collected data on cats’ signalment, clinical signs, results of physical examination, routine laboratory and thyroid hormone testing, and thyroid imaging (thyroid scintigraphy or ultrasound).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…[1][2][3][4]8,13 We could not . 33,34,36 Obviously, differentiating the cause of the high serum TSH concentrations (ie, NTIS vs hypothyroidism) is much more important in cats treated for hyperthyroidism that develop iatrogenic hypothyroidism, which is a common complication, 34,36 than in cats with naturally occurring hypothyroidism, which is a rare disorder. [32][33][34] Cats that died within 30 days of thyroid testing had lower serum T 4 , T 3 , and TSH concentrations than did the cats that survived, suggesting that these hormone test results could be used to predict short-term outcomes, as previously suggested for T 4 in cats with NTIS.…”
Section: Such Low Tsh Concentrations In Patients With Low Serum T 4 Amentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4]8,13 We could not . 33,34,36 Obviously, differentiating the cause of the high serum TSH concentrations (ie, NTIS vs hypothyroidism) is much more important in cats treated for hyperthyroidism that develop iatrogenic hypothyroidism, which is a common complication, 34,36 than in cats with naturally occurring hypothyroidism, which is a rare disorder. [32][33][34] Cats that died within 30 days of thyroid testing had lower serum T 4 , T 3 , and TSH concentrations than did the cats that survived, suggesting that these hormone test results could be used to predict short-term outcomes, as previously suggested for T 4 in cats with NTIS.…”
Section: Such Low Tsh Concentrations In Patients With Low Serum T 4 Amentioning
confidence: 99%
“…As in humans and dogs, recent studies have demonstrated the utility of serum TSH concentrations for diagnosing cats with iatrogenic and naturally occurring hypothyroidism. [31][32][33][34] However, only limited data on serum TSH concentrations have been reported in a small number of cats with NTIS associated with chronic kidney disease, in which serum TSH concentration were within the reference interval. 35,36 If cats with NTIS do occasionally develop high serum TSH concentrations, this finding could lead to an erroneous diagnosis of hypothyroidism, as reported in humans and dogs with NTIS.…”
Section: Introductionmentioning
confidence: 99%
“…Feline hypothyroidism is most frequently an iatrogenic consequence of therapy for hyperthyroidism (Welches et al 1989). Spontaneous hypothyroidism is uncommon, with only 11 cases of adult-onset disease (Rand et al 1993, Blois et al 2010, Galgano et al 2014, Kent et al 2016, Peterson et al 2018 and approximately 65 cases of congenital hypothyroidism reported (Arnold et al 1984, Peterson 1989, Sjollema et al 1991, Tanase et al 1991, Jones et al 1992, Peterson et al 1994, Stephan & Schütt-Mast 1995, Schumm-Draeger et al 1996, Firth et al 2000, Tobias & Labato 2001, Mazrier et al 2003, Crowe 2004, Szabo & Wells 2007, Traas et al 2008, Quante et al 2010, McGhie & Thompson 2011, Lim et al 2014, Peterson 2015, Van Bergen et al 2016, Jacobson & Rochette 2018.…”
Section: Introductionmentioning
confidence: 99%
“…2016, Peterson et al . 2018) and approximately 65 cases of congenital hypothyroidism reported (Arnold et al . 1984, Peterson 1989, Sjollema et al .…”
Section: Introductionmentioning
confidence: 99%
“…Hyperthyroidism, first described in cats in 1979, is the most common feline endocrinopathy in most developed nations. 1,2 Recognised options for management of feline hyperthyroidism include administration of radioiodine, chronic daily dosing with antithyroid medication (orally or transdermally) and surgical thyroidectomy. 1 More recently, an iodine-restricted prescription diet has become available in certain countries.…”
Section: Introductionmentioning
confidence: 99%